2004
DOI: 10.1158/0008-5472.can-04-0078
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens/Flavonoids Reverse Breast Cancer Resistance Protein/ABCG2-Mediated Multidrug Resistance

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
189
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(197 citation statements)
references
References 23 publications
7
189
0
1
Order By: Relevance
“…They also demonstrated that the mean BCRP protein level in the placenta was lower in homozygotes for the A421 allele than in those for the C421 allele and that heterozygotes had an intermediate level. 26 Although the molecular mechanism for the relationship between BCRP and carcinogenesis remains to be resolved, BCRP transports a wide variety of substances other than anticancer drugs, including fluorescent dyes, 27 sterols, 28 phytoestrogens, 29 chlorophyll derivatives 30 and folate. 31 Pheophorbide a, a chlorophyll derivative, was shown to have antimutagenic activity and to inhibit tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that the mean BCRP protein level in the placenta was lower in homozygotes for the A421 allele than in those for the C421 allele and that heterozygotes had an intermediate level. 26 Although the molecular mechanism for the relationship between BCRP and carcinogenesis remains to be resolved, BCRP transports a wide variety of substances other than anticancer drugs, including fluorescent dyes, 27 sterols, 28 phytoestrogens, 29 chlorophyll derivatives 30 and folate. 31 Pheophorbide a, a chlorophyll derivative, was shown to have antimutagenic activity and to inhibit tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Pgp activity was shown to be inhibited by curcumin, ginsenosides, piperine, some cathechins from green tea, quercetin, and silymarin [14,29,30]. Genistein is a substrate of BCRP and therefore acts as a competitive inhibitor of BCRP-mediated transport [31].…”
Section: Mechanisms Of Cam-anticancer Drug Interactionsmentioning
confidence: 99%
“…Many compounds have been shown to reverse BCRP-mediated drug resistance in vitro, including fumitremorgin C, an extract from Aspergillus fumigatus (20), GF120918, a compound developed as a P-glycoprotein inhibitor (21), estrogens like estrone and 17b-estradiol (22), novobiocin, a coumermycin antibiotic (23), and plant-derived hydroxyflavonoids such as genistein (24). Although BCRP inhibitors have been the subject of much investigation, relatively little research has been conducted in vivo on the reversing effects of BCRP inhibitors on drug resistance, and no inhibitor specifically targeting BCRP has been used in clinical trials.…”
Section: Introductionmentioning
confidence: 99%